Association between urinary metals levels and metabolic phenotypes in overweight and obese individuals. (September 2020) - Xu, Yali; Wei, Yue; Long, Tengfei; Wang, Ruixin; Li, Zhaoyang; Yu, Caizheng; Wu, Tangchun; He, Meian
Abstract: Epidemiologic studies suggest that circulating metals from the natural environment are linked with cardiometabolic health. However, few studies examined the relationship between multiple metals exposure and metabolic phenotypes, especially in obese individuals. We conducted a cross-sectional study to explore the association between 23 urinary metals and metabolic phenotypes in 1392 overweight and obese individuals (592 males, 800 females, mean age 43.1 ± 9.8 years). Participants were classified as metabolically unhealthy if they had ≥2 of the following metabolic abnormalities: elevated blood pressure, elevated fasting blood glucose, elevated triglycerides, and reduced high-density lipoprotein cholesterol. Odds ratios (ORs) of unhealthy metabolic phenotypes for metal levels categorized into tertiles were assessed using logistic regression models. Five metals (barium, copper, iron, uranium, and zinc) were associated with unhealthy metabolic phenotypes in single-metal models, while in the multiple-metal model, only zinc and zinc-copper ratio remained significant. The ORs (95% CIs) comparing extreme tertiles were 2.57 (1.69, 3.89) for zinc and 1.68 (1.24, 2.27) for zinc-copper ratio after adjustment for confounders (both p -trends were <0.001). The numbers of metabolic abnormalities significantly increased with the levels of zinc and the zinc-copper ratio increased. Similar associations were observed with metabolic syndrome risk. High levels of urinary zinc were positively associated with elevated fasting blood glucose ( p -trend < 0.001) and elevated triglycerides ( p -trend = 0.003). The results suggest that urinary zinc and zinc-copper ratio are positively associated with increased risk of unhealthy metabolic phenotype. Further prospective studies with a larger sample size are required to verify these findings. Graphical abstract: Image 1 Highlights: We assessed the associations between urinary levels of multiple metals and metabolic phenotypes in overweight and obese. Zinc and zinc-copper ratio were positively associated with the risk of unhealthy metabolic phenotype and MetS. With the levels of zinc and zinc-copper ratio increased, the number of metabolic abnormalities significantly increased.